2005
DOI: 10.1103/physrevb.72.115402
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion rates of Cu adatoms on Cu(111) in the presence of an adisland nucleated at fcc or hcp sites

Abstract: The surface diffusion of Cu adatoms in the presence of an adisland at FCC or HCP sites on Cu(111) is studied using the EAM potential derived by Mishin et al. [Phys. Rev. B 63 224106 (2001)]. The diffusion rates along straight (with close-packed edges) steps with (100) and (111)-type microfacets (resp. step A and step B) are first investigated using the transition state theory in the harmonic approximation. It is found that the classical limit beyond which the diffusion rates follow

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
61
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(74 citation statements)
references
References 66 publications
11
61
2
Order By: Relevance
“…For the 3p elements an exponent of 0.507 and a Meyer-Neldel energy of 0.014 eV, as well as a reference frequency ν 0 of 0.01 THz, is found. These parameters differ strongly from what has been found for the 4d and 5d TM impurities [61], and appear to be closer to other analyses [100,101]. However, an alternate Meyer-Neldel analysis of the computed log(D 0 ) versus H mig,2 values does not yield a significant correlation because the D 0 are similar for all impurity elements considered.…”
Section: Diffusivitiescontrasting
confidence: 48%
“…For the 3p elements an exponent of 0.507 and a Meyer-Neldel energy of 0.014 eV, as well as a reference frequency ν 0 of 0.01 THz, is found. These parameters differ strongly from what has been found for the 4d and 5d TM impurities [61], and appear to be closer to other analyses [100,101]. However, an alternate Meyer-Neldel analysis of the computed log(D 0 ) versus H mig,2 values does not yield a significant correlation because the D 0 are similar for all impurity elements considered.…”
Section: Diffusivitiescontrasting
confidence: 48%
“…Kurpick et al [8] and Marinica et al [4] have calculated the prefactors of a number of hopping mechanisms for self-diffusion of Ir and Cu clusters, and found that for all hopping mechanisms the prefactors were of the same order of magnitude as in a single atom diffusion. There is no hint of the large prefactor values found in experiments.…”
Section: Resultsmentioning
confidence: 97%
“…The phonon density of states (SðnÞ) of the clusters are obtained in the constant volume and constant energy ensemble at T ¼ 100 K, calculated for clusters by Fourier transform of the velocity auto-correlation function [4,12]:…”
Section: Simulation Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…The embedded atomic method (EAM) model was employed to describe the interaction potential between Cu atoms. The original parameters of Cu EAM were derived from Mishin et al [29], which have been proved to successfully model Cu crystal and cluster [30][31][32]. The Verlet method was used to integrate the classical equation of motion with a time-step of 2.5 fs.…”
Section: Simulation Detailsmentioning
confidence: 99%